2015
DOI: 10.1007/s12665-015-4576-3
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of potentially harmful elements in topsoils around Kerman city, southeastern Iran

Abstract: A multi-element geochemical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
1
6
2
Order By: Relevance
“…5b), therefore presenting minimal risk. The study by Atapour (2015) also found zinc to be elevated, and similar to the current study, the concentrations did not exceed Australia's guideline of 7400 mg kg −1 .…”
Section: Predicted Distribution Of Pb and Znsupporting
confidence: 85%
See 1 more Smart Citation
“…5b), therefore presenting minimal risk. The study by Atapour (2015) also found zinc to be elevated, and similar to the current study, the concentrations did not exceed Australia's guideline of 7400 mg kg −1 .…”
Section: Predicted Distribution Of Pb and Znsupporting
confidence: 85%
“…Previous studies have also linked land use to elevated metal concentrations in the soil (Atapour, 2015;Facchinelli et al, 2001;Guagliardi et al, 2015;Lin et al, 2002;Snowdon and Birch, 2004). The unexpected finding may have been a result of differing contaminant sources, interactions between other covariates in the model, or due to unavailable zoning data within the land use dataset (land use class 'unknown' represented 20.4% of catchment).…”
Section: Drivers Of Pb and Zn Distribution In The Sydney Estuary Catcmentioning
confidence: 93%
“…The natural concentrations of trace elements in soil play a key role in controlling the impact caused by humans and in the level of soil quality of an area [ 5 , 6 , 7 ]. Studies of soil contaminated by heavy metals have identified areas with a high risk of pollution through the analysis of atypical local spatial values [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cr had the maximum content of 35 mg/kg equal to its value in the background soil. It was reported the mean concentration of Cr equal to 36.9 mg/kg in topsoil around Kerman in the study by Atapour (Atapour 2015 ). The maximum concentration of Cu (148 mg/kg) in the western part of Kerman could be associated to the copper industry situated in this section.…”
Section: Resultsmentioning
confidence: 99%
“…As value in the street dust samples in Tehran, the capital of Iran, was reported about 6 mg/kg (Taghavi et al 2019 ). The sources of As could be associated to the natural sources, particularly from deserts and agricultural or industrial activities (Atapour 2015 ). The mean concentration of Cd was similar to its value in the background sampling point (0.34 mg/kg).…”
Section: Resultsmentioning
confidence: 99%